2022
DOI: 10.1186/s12985-022-01812-3
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Torquetenovirus (TTV) microRNAs and severity of COVID-19

Abstract: Background Torquetenovirus (TTV), a widespread anellovirus recognized as the main component of the healthy human virome, displays viremia that is highly susceptible to variations in immune competence. TTV possesses microRNA (miRNA)-coding sequences that might be involved in viral immune evasion. Among TTV-encoded miRNAs, miRNA t1a, t3b, and tth8 have been found in biological fluids. Here, the presence of TTV DNA and TTV miRNAs in the plasma of severe acute respiratory syndrome coronavirus 2 (SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…When combined, TTV DNA load and SARS-CoV-2 viremia allowed to predict the outcome of COVID-19 infection, with a higher risk (HR=12.4) of ICU admission in patients with low TTV DNA load and positive SARS-CoV-2 viremia ( 3 ). Stincarelli et al reported that serum TTV DNA seems unrelated to COVID-19 severity, while TTV miRNA tth8 seems related ( 4 ). At the other end of the spectrum, Emmel et al found that the 100-day survival rate in cancer patients who died from COVID-19 was significantly lower in the TTV-positive group than in the TTV-negative group (P = 0.0475), and that in the cancer TTV-positive group, those who died also had a higher load of TTV than those who did not die (P = 0.0097) ( 5 ).…”
mentioning
confidence: 99%
“…When combined, TTV DNA load and SARS-CoV-2 viremia allowed to predict the outcome of COVID-19 infection, with a higher risk (HR=12.4) of ICU admission in patients with low TTV DNA load and positive SARS-CoV-2 viremia ( 3 ). Stincarelli et al reported that serum TTV DNA seems unrelated to COVID-19 severity, while TTV miRNA tth8 seems related ( 4 ). At the other end of the spectrum, Emmel et al found that the 100-day survival rate in cancer patients who died from COVID-19 was significantly lower in the TTV-positive group than in the TTV-negative group (P = 0.0475), and that in the cancer TTV-positive group, those who died also had a higher load of TTV than those who did not die (P = 0.0097) ( 5 ).…”
mentioning
confidence: 99%
“…However, this association was observed at a time when lymphocyte counts were notably lower in severe cases during the second week after symptom onset 25 . In small group of 56 SARS‐CoV‐2 infected patients, Stincarelli et al did not observe a correlation between TTV load in plasma and disease severity but identified a significant association between severe progression and TTV miRNA tth8 26 …”
Section: Discussionmentioning
confidence: 96%
“…week period between severe and mild-moderate SARS-CoV-2 cases, Solis et al demonstrated that a TTV DNA load lower than 700 copies/mL was linked to a higher risk of severe COVID-19.However, this association was observed at a time when lymphocyte counts were notably lower in severe cases during the second week after symptom onset 25. In small group of 56 SARS-CoV-2 infected patients, Stincarelli et al did not observe a correlation between TTV load in plasma and disease severity but identified a significant association between severe progression and TTV miRNA tth8 26. F I G U R E 1 Probability of ICU admission according to TTV load.…”
mentioning
confidence: 97%
“…Based on what previous studies show us, the aforementioned v-miRNAs can be identified and reported in both viremic and non-viremic individuals. ttv-miRNAs are involved in escaping from the host's immune system, viral reactivation, as well as pathogenicity, and finally maintaining chronic viral infection and helping the virus in these processes [ 65 , 75 , 76 ]. TTV uses the cellular miRNA-making machinery to encode and synthesize its viral miRNAs and use them to activate or inhibit specific intracellular signaling pathways [ 77 ].…”
Section: The Role Of Ttv-mirna In Human Diseasementioning
confidence: 99%
“…The amount of viral load of TTV in the plasma of people with AIDS shows a noticeable decrease after starting the treatment of these patients [ 155 ]. TTV-specific miRNAs were observed in the plasma and cerebrospinal fluid of patients infected with HIV, HCV, or HBV [ 65 ]. Also, high TTMV DNA load has been observed in tissues such as bone marrow and spleen of people who are HIV positive or have progressed to AIDS [ 12 ].…”
Section: Viral Infectionmentioning
confidence: 99%